Differences in Exposure to Nicotine, Tobacco-Specific Nitrosamines, and Volatile Organic Compounds among Electronic Cigarette Users, Tobacco Smokers, and Dual Users from Three Countries - Danielle M. Smith; Lion Shahab; Benjamin C. Blount; Michal Gawron; Leon Kosminder; Andrzej Sobczak; Baoyun Xia; Connie S. Sosnoff; Maciej L. Goniewicz (Toxics, 2020)
Country-level differences in nicotine vaping products used and biomarkers of exposure among long-term e-cigarette users and dual users remain understudied. This cross-sectional study was conducted in 2014 in the United States (n = 166), United Kingdom (n = 129), and Poland (n = 161). We compared patterns of tobacco product use and nicotine and toxicant exposure among cigarette-only smokers (n = 127); e-cigarette-only users (n = 124); dual users of tobacco cigarettes and e-cigarettes (n = 95); and non-users (control group, n = 110) across three countries using mixed-effects linear regression. Compared with cigarette smokers, e-cigarette-only users had lower levels of toxicant biomarkers, but higher levels of nicotine biomarkers. Dual users had higher levels of toxicant biomarkers than e-cigarette-only users but similar levels to cigarette-only smokers. E-cigarette users in Poland, who overwhelmingly used refillable tank devices, exhibited greater levels of nicotine, and toxicant biomarkers relative to e-cigarette users in US/UK. Despite smoking fewer cigarettes, dual users from Poland exhibited similar levels of nicotine biomarkers compared with UK dual users, but higher than US dual users. Country-level differences in e-cigarette devices used and smoking behaviors (e.g., intensity) may contribute to differences in biomarker levels among users of the same products residing in different countries.